Femtosecond laser fabricated polymer microring resonator for sensing applications. Issue 14 (1st July 2018) - Zhang, D.; Men, L.; Chen, Q.
Abstract : A microring resonator realised by femtosecond laser two‐photon photopolymerisation in an epoxy‐based negative photoresist (SU‐8) is proposed and demonstrated, which is further proved to be capable of temperature and refractive index sensing by monitoring the shift of the resonance wavelength of the interferometric pattern. The experimental results indicate refractive index sensitivity of 12.50 nm/refractive index unit (redshift) and temperature sensitivity of −9.51 × 10 −2 nm/ o C (blueshift), respectively.